Interpretation of Customary International Law : Of Methods and Limits - Merkouris, Panos, (Brill Research Perspectives in International Law., 2024)
In international law interpretation is ubiquitous. However, whereas in the case of treaty interpretation, this process has been codified in Articles 31-33 of the Vienna Convention on the Law of Treaties, the interpretation of rules of customary international law has remained largely unexplored. This monograph demonstrates not only that rules of customary international law can be interpreted but also that they have continuously been interpreted by international and domestic courts. Through an examination of this case-law, the various methods of interpretation of customary rules and their limits are identified as well as the similarities and differences with the rules of treaty interpretation.